Respiratory outcome of spinal muscular atrophy type 1 patients treated with nusinersen - ERGENEKON, ALMALA PINAR; ÖZTÜRK THOMAS, GÜLTEN; ÜNVER, OLCAY; TÜRKDOĞAN, DİLŞAD; KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA (My University, 2022)
Background Respiratory failure is the leading cause of mortality in spinal muscular atrophy type 1 (SMA1) children. The current study aims to evaluate the effect of nusinersen treatment on respiratory outcome of the patients with SMA1. Methods In this retrospective, single-center study, 52 SMA1 patients treated with nusinersen were included in the analysis. Patients were divided into two groups based on their age at the time of their first nusinersen treatment (Group 1: 6 months). Respiratory outcome on the 180th day of treatment is defined as the type of ventilation support (spontaneous breathing, noninvasive ventilation (NIV), and tracheostomized or intubated on invasive mechanical ventilation). Demographic data, respiratory outcome, and Children\"s Hospital of Philadelphia Infant Test of Neuromuscular Disorders scores were obtained from medical records. Results On the 180th day of treatment, 46 of the 52 (88.4%) children were alive. Prevalence of the mortality was similar in both groups (P = 0.65). The comparison of respiratory outcome in patients between group 1 and group 2 was as follows: spontaneous breathing, 7 (43.7%) versus 4 (13.3%) (P = 0.03); NIV = 16 h/day. There were significant improvements in Children\"s Hospital of Philadelphia Infant Test of Neuromuscular Disorders scores of the patients at day 180 in comparison with the baseline (P < 0.001). Conclusions Early initiation of nusinersen treatment in SMA1 patients may alter the disease\"s natural course.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; nusinersen; respiratory follow up; treatment; CONSENSUS STATEMENT; CARE; SMA; MANAGEMENT; DIAGNOSIS; STANDARD; CHILDREN; INFANTS